PETER PAN - O'Flarherty, David Desmond; Barrie, James M. (James Matthew); Pipchenko, Ludmila; Naguran, Mallika; Lee, Daniele (Singapore : WS Education, an imprint of World Scientific Publishing Co. Pte. Ltd., 2022)
"Life with Peter Pan is hardly dull! The boy who never grows up takes Wendy and her brothers on a wild adventure. With fairy Tinker Bell, they fly far, far away to Neverland. There, they live under a tree with the Lost Boys and hide from the pirates. Follow Peter and friends in their fantasies until bloodthirsty Hook creeps up. Can they escape? Tick tick tick..."--Back cover.
Adaptation of (work): Barrie, J. M. (James Matthew), 1860-1937. Peter Pan.
Keywords: Peter Pan (Fictitious character) -- Juvenile fiction; Children's stories (English); Never-Never Land (Imaginary place) -- Juvenile fiction; Adaptations